2023
DOI: 10.1039/d2fo03263e
|View full text |Cite
|
Sign up to set email alerts
|

Bifidobacterium longum subsp. infantis FJSYZ1M3 ameliorates DSS-induced colitis by maintaining the intestinal barrier, regulating inflammatory cytokines, and modifying gut microbiota

Abstract: B. longum subsp. infantis was a subspecies of Bifidobacterium longum, and very few strains were shown to have immunomodulatory effects. In the present study, the improvement of dextran sulphate sodium...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…lactis HY8002, and B. longum subsp. infantis BB-02) can repair disease-induced damage to the intestinal barrier and upregulate tight junction protein expression [40][41][42] . We found that supplementation of B. longum subsp.…”
Section: Discussionmentioning
confidence: 99%
“…lactis HY8002, and B. longum subsp. infantis BB-02) can repair disease-induced damage to the intestinal barrier and upregulate tight junction protein expression [40][41][42] . We found that supplementation of B. longum subsp.…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of myeloperoxidase (MPO), an enzyme predominantly expressed and released by neutrophils, are indicative of the degree of colonic neutrophil infiltration and tissue damage. 11 Notably, dysbiosis of the gut microbiota is a common occurrence in both IBD patients and mice. Hence, rectifying gut microbiota dysbiosis has emerged as a promising therapeutic approach for managing intestinal inflammation.…”
Section: ■ Discussionmentioning
confidence: 99%
“…A prior clinical trial found that combining B. longum trisporus with mesalazine improved the therapeutic effect of drugs used for UC ( Jiang et al, 2020 ), inferring that trisporus could be a safe and convenient supplementary treatment option for patients who are resistant to traditional medications. Overall, B. longum may be a useful adjuvant biologic drug in the treatment of UC ( Li et al, 2023 ).…”
Section: Therapeutic Effects Of Probiotics On Ucmentioning
confidence: 99%
“…It is acid- and bile-resistant, is strongly adhesive, does not destroy mucus, is non-invasive, and does not harm the intestinal mucosa ( Ewaschuk et al, 2008 ). B. infantis FJSYZ1M3 can remarkably reduce the DAI, limit weight loss and colonic shortening via alteration of the gut microbiota, maintain the integrity of the intestinal barrier, and modulate levels of inflammatory cytokines ( Li et al, 2023 ). B. infantis also enhances the development of cluster of differentiation (CD) 4+ T cells into Tregs and also increases the expression of IL-10 and TGF-β1, subsequently reducing the inflammatory response in the gut ( Zhou et al, 2022 ).…”
Section: Therapeutic Effects Of Probiotics On Ucmentioning
confidence: 99%